2018
DOI: 10.3390/molecules23092342
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Skin-Moisturizing Effects of a Flavonoid Glycoside Extracted from the Aquatic Plant Nymphoides indica in Human Keratinocytes

Abstract: Nymphoides indica, an aquatic plant, is used as folk medicine in some countries. Our previous study demonstrated that the methanol extract of N. indica inhibited the activity of tyrosinases, tyrosine related protein (TRP)1 and TRP2, and microphthalmia-associated transcription factor, as well as the activity of protein kinase A, by effectively inhibiting cyclic adenosine monophosphate. Although the biological activities of N. indica extract have been reported, there are no reports on the skin bioactivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In addition, botanical extracts have been shown to prevent or alleviate skin wrinkles caused by the secretion of inflammatory cytokines while promoting collagen production. Therefore, based on our results, we hypothesize that V. uliginosum extract effectively prevents skin photoaging by reducing the production of MMPs [35][36][37].…”
Section: Discussionmentioning
confidence: 67%
“…In addition, botanical extracts have been shown to prevent or alleviate skin wrinkles caused by the secretion of inflammatory cytokines while promoting collagen production. Therefore, based on our results, we hypothesize that V. uliginosum extract effectively prevents skin photoaging by reducing the production of MMPs [35][36][37].…”
Section: Discussionmentioning
confidence: 67%
“…Although the pathogenesis of ACD is not fully known, multiple studies reported that inflammatory and pruritic mediators are involved in the progress of ACD ( Nedoszytko et al., 2014 ). T helper (Th) 2 cytokines are typical inflammatory mediators in ACD ( Kim et al., 2018 ). In addition, recruitment of nerve growth factor (NGF) and interleukin (IL)-31 induces severe itching in ACD ( Feld et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are polyphenols largely spread in plants, which are ingredients in fruits, herbal medicines and teas [7]. Quercetin 3,7-dimethyl ether 4'-glucoside isolated from the aquatic plant Nymphoides indica [8], puerarin V, an isoflavone isolated from the Chinese herb Kudzu (Pueraria spp.) root [9] and pilloin, from the stem barks of Aquilaria sinensis [7] showed anti-inflammatory activity in diverse models.…”
mentioning
confidence: 99%
“…root [9] and pilloin, from the stem barks of Aquilaria sinensis [7] showed anti-inflammatory activity in diverse models. For example, the effect of quercetin 3,7-dimethyl ether 4'-glucoside on diverse inflammatory markers after ultraviolet B irradiation of keratinocytes (HaCaT) was evaluated [8]. The authors reported that this flavonoid could inhibited p38, JNK, ERK (extracellular-signal-regulated kinase) and IκBα phosphorylation and inhibits the NF-κB expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation